Die-casting alloy material for hybrid engine case and processing method of die-casting alloy material
By employing a sandwich structure and Al-Si phase change microcapsule design in the engine compartment of a hybrid vehicle, noise and vibration management issues were addressed, resulting in noise reduction and vibration attenuation, and improved overall performance and reliability.
Patent Information
- Application Number
- CN202511000685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-11-18
AI Technical Summary
Under the complex load spectrum and lightweight requirements of the powertrain, the engine box of hybrid electric vehicles is difficult to effectively manage noise, vibration and heat management with existing materials, resulting in noise pollution and vibration transmission and diffusion, which affects the comfort and reliability of the whole vehicle.
Employing a sandwich structure of rigid layer-damping layer-rigid layer, combined with Al-Si phase change microcapsules and viscoelastic damping materials, acoustic and vibrational energy are converted into thermal energy through the Helmholtz resonance effect and the molecular chain slippage motion of the viscoelastic damping material, and then rapidly discharged through a high thermal conductivity substrate material.
This reduces noise pollution, decreases vibration acceleration, improves the comfort of the operating environment and the thermal stability of the engine, extends the life of components, and reduces maintenance costs.
Smart Images

Figure CN120963144A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of manufacturing non-ferrous metal alloys such as metal matrix composites, and particularly to a die-casting alloy material for hybrid engine housings and its processing method. Background Technology
[0002] Hybrid electric vehicles (HEVs) are a key technology in the automotive industry's transition to electrification, and the performance of their powertrains is crucial. The engine block (typically referring to a structural component integrating the crankcase, transmission housing, and motor housing) is the core component of the powertrain, directly affecting the vehicle's power performance, reliability, lightweight level, and NVH (noise, vibration, and harshness) performance. Die-cast aluminum alloys, with their excellent casting fluidity, high production efficiency, superior mechanical properties, and significant lightweight advantages, have long been the preferred material for manufacturing traditional internal combustion engine cylinder blocks, cylinder heads, and transmission housings.
[0003] However, the operating environment of hybrid systems places more stringent demands on the engine housing. The hybrid housing must simultaneously withstand the combustion impact of the internal combustion engine, the reciprocating inertial force of the pistons, the unbalanced rotational force of the crankshaft, and the electromagnetic excitation force and high-speed centrifugal force of the drive motor. The power source frequently switches between multiple modes, including pure electric drive, hybrid drive, engine direct drive, and energy recovery, resulting in an extremely complex and variable load spectrum on the housing. Simultaneously, to offset battery weight and improve energy efficiency, the requirements for lightweighting the housing have reached unprecedented levels. Furthermore, the improved quietness in electric vehicle mode makes consumers more sensitive to the noise level of the vehicle in hybrid mode, placing near-stringent standards on the NVH performance of the powertrain. Summary of the Invention
[0004] This invention overcomes the shortcomings of the prior art and provides a die-casting alloy material for hybrid engine housings and its processing method.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a die-casting alloy material for hybrid engine housings and its processing method, comprising the following steps:
[0006] S1: A non-ferrous metal matrix composite material with both rigidity and thermal conductivity is used as the base material, and is uniformly mixed with Al-Si phase change microcapsules and pressed into a heat dissipation preform.
[0007] S2: Mix the base material powder with low melting point metal wire, prepress and solidify, and heat to dissolve the metal wire to obtain a rigid layer preform;
[0008] S3: Mix and press the base material powder with the damping material to obtain the damping layer preform;
[0009] S4: The products of S1, S2 and S3 are stacked in sequence as rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform, preheated and pressed into shape.
[0010] In a preferred embodiment of the present invention, in S1, the rigidity is specifically an elastic modulus of 70-80 GPa, the thermal conductivity is specifically a thermal conductivity of 145-155 W / mK, and the substrate is selected from one of high silicon aluminum alloy, aluminum-magnesium alloy or silicon-copper alloy.
[0011] In a preferred embodiment of the present invention, in S1, the Al-Si phase change microcapsules are specifically prepared as follows:
[0012] A1: The Al-Si alloy is ground into granules and then oxidized under high pressure to form an aluminum hydroxide transition layer;
[0013] A2: The A1 product is placed in an oxygen environment and heated to transform the transition layer into an alumina shell.
[0014] A3: The A2 product is immersed in silica sol and heated to allow the alumina and silica to react and form a mullite shell, thus obtaining Al-Si phase change microcapsules.
[0015] In a preferred embodiment of the present invention, in A1, the particle diameter is 20-50 μm, the high-pressure environment is specifically 0.5-2 MPa with water vapor introduced, the temperature is 100-150℃, and the time is 0.5-1 h.
[0016] In a preferred embodiment of the present invention, in A2, the heating process specifically involves a heating rate of 20-30℃ / min, a final temperature of 700-1100℃, and a holding time of 0.5-6h; in A3, the heating temperature is 1000-1200℃.
[0017] In a preferred embodiment of the present invention, in S2, the low-melting-point metal wire is selected from one of low-temperature aluminum welding wire, lead-tin alloy or aluminum bronze welding wire. The pre-pressing and curing specifically involves first cold pressing under a pressure of 200-300MPa, and then hot pressing at a pressure of 70-100MPa at a temperature of 350-400℃; the heating and melting temperature is 450-500℃.
[0018] In a preferred embodiment of the present invention, in S3, the mixing and pressing parameters are a pressure of 40-50 MPa.
[0019] In a preferred embodiment of the present invention, in S4, the preheating parameters are: the temperature is raised to 350-400℃ for 10-20 minutes; the pressing molding specifically involves placing the preheated product into the mold cavity, melting the base material at 680-720℃ and injecting it into the mold cavity at a speed of 0.2-0.5 m / s, and then applying high-speed pressurization at a speed of 3-5 m / s and a pressure of 70-100 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole.
[0020] A die-cast alloy material for a hybrid engine housing includes a heat dissipation layer and a sound-absorbing layer; the sound-absorbing layer is disposed near the interior of the engine housing and has a sandwich structure; the heat dissipation layer is disposed away from the interior of the engine housing.
[0021] In a preferred embodiment of the present invention, the sound-absorbing layer sandwich structure is specifically a rigid layer-damping layer-rigid layer, with a plurality of sound-absorbing holes formed on the rigid layer.
[0022] This invention addresses the shortcomings of the prior art and has the following beneficial effects:
[0023] (1) This invention provides a die-cast alloy material for hybrid engine housing and its processing method. By adopting a sandwich structure of rigid layer-damping layer-rigid layer sound-absorbing layer and having specially designed sound-absorbing holes, sound waves are repeatedly reflected and interfered in the channel. By utilizing the Helmholtz resonance effect and the viscous sliding motion of the molecular chains of viscoelastic damping material (i.e., polyimide microspheres), sound energy is efficiently converted into heat energy. Compared with the pure metal or simple sound insulation layer design in the prior art (such as aluminum alloy housing without layered structure), this technology avoids the problem of low efficiency caused by only partially absorbing or scattering sound wave energy. Furthermore, this mechanism not only reduces noise pollution, but also improves the operating environment comfort of hybrid engine and reduces sound wave interference to electronic components.
[0024] (2) This invention provides a die-cast alloy material for hybrid engine housings and its processing method. By utilizing the inner and outer rigid layers in a sandwich structure to constrain the intermediate damping layer, the damping material is forced to undergo high-intensity shear deformation under alternating loads. The repeated sliding friction of the molecular chains converts vibrational mechanical energy into heat energy. Based on the vibration acceleration of 24Hz in Example 1, this structure achieves a direct effect of 50%-60% vibration acceleration attenuation. Compared with existing engine housings with a single rigid layer (vibration acceleration is often 60-70Hz), this design avoids resonance problems caused by vibration transmission, diffusion, and energy accumulation. Furthermore, this vibration energy conversion mechanism extends the lifespan of the engine housing and related components, reducing maintenance costs and the risk of mechanical failure.
[0025] (3) This invention provides a die-cast alloy material for hybrid engine housings and its processing method. By uniformly dispersing Al-Si phase change microcapsules on the heat dissipation layer substrate material, the heat absorption capacity of the phase change material is utilized to smooth temperature fluctuations, and combined with a high thermal conductivity substrate for rapid heat conduction. In Example 1, the microcapsule addition of 22% can maintain a direct effect within a temperature gradient of 0.8℃ / mm, preventing damping material failure and thermal deformation. Compared with the heat dissipation design without phase change materials in the prior art (such as pure aluminum heat dissipation layers), this technology solves the problem of local overheating caused by transient heat peaks (the peak temperature in the prior art often exceeds 150℃). Furthermore, this thermal management not only enhances the acoustic-to-thermal energy conversion efficiency but also improves the overall thermal stability of the engine, ensuring the reliable operation of the hybrid system under high-temperature conditions. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a three-dimensional structural diagram of a preferred embodiment of the present invention. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0030] As shown in the figure, a die-casting alloy material for hybrid engine housing and its processing method include the following steps: S1: A non-ferrous metal matrix composite material with both rigidity and thermal conductivity is used as the base material and uniformly mixed with Al-Si phase change microcapsules, and pressed into a heat dissipation preform; S2: The base material powder is mixed with low melting point metal wire, pre-pressed and cured, and heated to dissolve the metal wire to obtain a rigid layer preform; S3: The base material powder is mixed with damping material and pressed to obtain a damping layer preform; S4: The products of S1, S2 and S3 are stacked in sequence according to the rigid layer preform-damping layer preform-rigid layer preform-heat dissipation preform, preheated and pressed into shape.
[0031] A die-cast alloy material for a hybrid engine housing includes a heat dissipation layer and a sound-absorbing layer; the sound-absorbing layer is disposed near the interior of the engine housing and has a sandwich structure; the heat dissipation layer is disposed away from the interior of the engine housing; the sandwich structure of the sound-absorbing layer is specifically a rigid layer-damping layer-rigid layer, and the rigid layer has a plurality of sound-absorbing holes.
[0032] It should be noted that the die-casting alloy material and its processing method of this application use a high-rigidity and high-thermal-conductivity material as the base material. Specifically, the base material is a non-ferrous metal alloy among metal matrix composites. Moreover, the engine box finally manufactured is made by die casting. The base material still adopts a layered design during the manufacturing process, consisting of a sound-absorbing layer and a heat-dissipating layer. The sound-absorbing layer is located near the interior of the engine box, and the heat-dissipating layer is located away from the interior of the engine box. The main body of the heat-dissipating layer is made by uniformly mixing the base material with Al-Si phase change alloy microcapsules. The phase change material microcapsules are uniformly mixed inside the base material. When heated, the Al-Si phase change alloy absorbs heat and undergoes a phase change, which is then transported to the outside through the base material. The sound-absorbing layer is made by mixing the base material with a viscoelastic material, thus forming a damping layer and a rigid layer. The base material is the rigid layer, and the viscoelastic material is the damping layer. Furthermore, it features a sandwich structure of a rigid layer, a damping layer, and another rigid layer. By restricting the lateral displacement of the damping layer, the damping adhesive is forced to undergo high-intensity shear deformation. Under shear stress, the molecular chains repeatedly slide and rub, converting mechanical vibration energy into heat energy, which is then transferred out through the base material. Additionally, several sound-absorbing holes are also provided on the rigid layer. Sound waves are repeatedly reflected between the rigid and damping layers, similarly converting sound energy into heat energy. This achieves the effect of dissipating internal sound waves by converting them into heat energy, thereby reducing the vibration radiated by sound waves to the engine compartment and reducing noise generation. The sandwich structure of the rigid layer, damping layer, and another rigid layer, by restricting the lateral displacement of the damping layer, forces the damping adhesive to undergo high-intensity shear deformation. Under shear stress, the molecular chains repeatedly slide and rub, converting mechanical vibration energy into heat energy, thus releasing the vibration as well.
[0033] In summary, by reducing the vibration induced by internal sound wave radiation to the engine housing, combined with the external engine housing structure itself converting vibration into heat energy for dissipation, noise generation is significantly reduced. The core lies in the step-by-step interception and heat energy conversion of sound wave radiation noise and structural vibration noise. When high-frequency sound waves generated by the mechanical movement inside the engine radiate towards the housing, the microporous array on the inner side of the anechoic layer first forms a sound wave trap. Utilizing the Helmholtz resonance effect and the repeated reflection and interference of sound waves within the channels, the sound wave energy is directly converted into frictional heat energy. The sound energy that is not completely dissipated continues to penetrate the inner rigid plate and is absorbed by the intermediate viscoelastic damping material, further converted into heat energy through the viscous sliding motion of the polymer molecular chains. Simultaneously, engine vibration is transmitted to the housing wall panels, causing structural noise. The inner and outer rigid layers in the sandwich structure strongly constrain the intermediate damping layer, forcing the damping material to undergo high-intensity shear deformation under alternating loads. The repeated sliding friction of the molecular chains efficiently converts the vibrational mechanical energy into heat energy. The heat generated by these two conversions is rapidly dissipated through a highly thermally conductive substrate material and an outer heat dissipation layer. The Al-Si phase-change microcapsules embedded in the heat dissipation layer absorb peak thermal energy, significantly smoothing temperature fluctuations within the enclosure. Ultimately, through the sound energy interception mechanism of the sound-absorbing holes and the vibration shearing mechanism of the sandwich structure, the solution essentially unifies airborne and solid-borne sound into manageable heat energy, disintegrating noise energy at its source and achieving a synergistic silencing effect of reducing sound pressure level by 8-12 dB and attenuating vibration acceleration by 50%-60%.
[0034] Example 1
[0035] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 22% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0036] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0037] The base material powder and the damping material are mixed and pressed. The damping material is selected as polyimide microspheres. The damping material accounts for 35% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0038] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in sequence according to the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, and then slowly pressing it. High-speed pressurization is then carried out at a speed of 4 m / s and a pressure of 80 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole, thus obtaining the die-cast alloy material for the hybrid engine box.
[0039] Example 2
[0040] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 25% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0041] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0042] The base material powder and the damping material are mixed and pressed. The damping material is selected as polyimide microspheres. The damping material accounts for 35% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0043] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in sequence according to the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, and then slowly pressing it. High-speed pressurization is then carried out at a speed of 4 m / s and a pressure of 80 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole, thus obtaining the die-cast alloy material for the hybrid engine box.
[0044] Example 3
[0045] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 15% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0046] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0047] The base material powder and the damping material are mixed and pressed. The damping material is selected as polyimide microspheres. The damping material accounts for 35% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0048] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in sequence according to the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, and then slowly pressing it. High-speed pressurization is then carried out at a speed of 4 m / s and a pressure of 80 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole, thus obtaining the die-cast alloy material for the hybrid engine box.
[0049] Example 4
[0050] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 22% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0051] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0052] The base material powder and the damping material are mixed and pressed together. The damping material is selected as polyimide microspheres. The damping material accounts for 30% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0053] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in sequence according to the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, and then slowly pressing it. High-speed pressurization is then carried out at a speed of 4 m / s and a pressure of 80 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole, thus obtaining the die-cast alloy material for the hybrid engine box.
[0054] Example 5
[0055] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 22% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0056] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0057] The base material powder and the damping material are mixed and pressed. The damping material is selected as polyimide microspheres. The damping material accounts for 40% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0058] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in sequence according to the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, and then slowly pressing it. High-speed pressurization is then carried out at a speed of 4 m / s and a pressure of 80 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole, thus obtaining the die-cast alloy material for the hybrid engine box.
[0059] Example 6
[0060] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 22% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0061] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0062] The base material powder and the damping material are mixed and pressed. The damping material is selected as polyimide microspheres. The damping material accounts for 35% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0063] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, then slowly pressing it. High-speed pressurization is then performed at a speed of 3 m / s and a pressure of 80 MPa, allowing the melt to penetrate into the gaps between the preforms and bond together to form a whole. This yields the die-cast alloy material for the hybrid engine housing.
[0064] Example 7
[0065] A non-ferrous metal matrix composite material with a high silicon aluminum alloy having both an elastic modulus of 75 GPa and a thermal conductivity of 150 W / mK was used as the base material and uniformly mixed with Al-Si phase change microcapsules. The amount of phase change microcapsules added was 22% of the total amount of the base material and the phase change microcapsules. The mixture was then pressed into a heat dissipation prefabricated block. Specifically, the Al-Si phase change microcapsules were made by grinding Al-Si alloy into particles with a diameter of 35 μm, oxidizing them under high pressure of 1.3 MPa with steam at a temperature of 125 °C for 0.8 h to form an aluminum hydroxide transition layer, placing them in an oxygen environment, and heating them at a heating rate of 25 °C / min to a final temperature of 900 °C for 3 h to transform the transition layer into an aluminum oxide shell. The temperature was then raised to 1100 °C, causing the aluminum oxide to react with silicon dioxide to form a mullite shell, thus obtaining the Al-Si phase change microcapsules.
[0066] The base material powder and low-melting-point metal wire, specifically low-temperature aluminum welding wire, are mixed, pre-pressed, and cured. The amount of low-melting-point metal wire added is 12% of the total amount of base material and low-melting-point metal wire in this step. The pre-pressing and curing process involves first cold pressing under a pressure of 250 MPa, then heating to 380°C, and hot pressing under a pressure of 85 MPa to dissolve the metal wire. The dissolution temperature is 475°C, resulting in a rigid layer preform.
[0067] The base material powder and the damping material are mixed and pressed. The damping material is selected as polyimide microspheres. The damping material accounts for 35% of the total amount of damping material and base material in this step. The mixing and pressing parameters are a pressure of 45MPa to obtain the damping layer preform.
[0068] The heat dissipation preform, rigid layer preform, and damping layer preform are stacked in the following order: rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform. The preheating process involves raising the temperature to 380℃ for 25 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 700℃ and injecting it into the mold cavity at a speed of 0.3 m / s, and then slowly pressing it. High-speed pressurization is then performed at a speed of 5 m / s and a pressure of 80 MPa, allowing the melt to penetrate into the gaps between the preforms and bond together to form a whole. This process yields the die-cast alloy material for the hybrid engine housing.
[0069] Experiment 1
[0070] The engines were prepared according to the seven preparation methods described in Examples 1 to 7. The prepared products were then assembled into complete engines in the same manner and tested sequentially in a closed space using different methods. Noise levels within the closed space were detected using a noise analyzer, and vibration acceleration of the different engines during operation was detected using a vibration sensor. Details are shown in Table 1.
[0071] Table 1
[0072]
[0073] As can be seen from Table 1,
[0074] As can be seen from Examples 1, 2, and 3, phase change microcapsules absorb peak thermal energy from the engine compartment through solid-liquid phase change. When the microcapsules are insufficient, the heat storage capacity cannot suppress high-temperature shocks, and the local temperature of the housing exceeds 150°C, leading to a dual failure. On the one hand, it stiffens the molecular chains of the damping material, reducing its shear deformation capacity; on the other hand, it causes thermal expansion and deformation of the metal matrix, increases the distortion rate of the sound-absorbing hole structure, destroys the original sound wave reflection path, and reduces the conversion efficiency of sound energy to heat energy. Conversely, excessive addition blocks the continuous thermal conductivity network of the substrate material, causing heat accumulation and forming a temperature difference zone, forcing the damping layer to soften and the rigid layer to crack. Only when the proportion of 22% forms a "lattice-like thermal buffer" can the matrix maintain thermal conductivity when the microcapsules are uniformly dispersed, and the surface temperature gradient is suppressed within 0.8°C / mm, ensuring the geometric accuracy of the sound-absorbing holes and the activity of the damping molecules, providing a stable thermal environment for the conversion of sound energy and vibration energy.
[0075] As can be seen from Examples 1, 4, and 5, viscoelastic damping microspheres undergo periodic shear deformation under the constraint of a rigid layer, converting mechanical energy into thermal energy through molecular chain slip friction. When the proportion of microspheres is less than 30%, the sparse distribution leads to a reduction in the effective shear area, and the excessive spacing between molecular chains results in energy being mainly converted into reversible elastic potential energy, insufficient vibrational energy thermal conversion rate, and attenuation of the box resonance peak acceleration. At the same time, the viscous resistance is insufficient when sound waves penetrate the sparse damping layer, reducing the sound energy dissipation efficiency. An excessively high proportion (>40 vol%) overturns the fundamental structure, with polymer microspheres compressing the metal matrix and destroying the rigid constraint framework. Vibrational energy is converted into low-frequency large deformation rather than thermal energy, and the decrease in sound wave propagation speed leads to a shift in the resonance frequency. A golden ratio of 35 vol% constructs a "molecular-scale dissipation network." The entangled structure with a microsphere spacing of approximately 30 nm, at the engine's 9 Hz main vibration frequency, enables molecular chain slip friction to generate a 38% thermal conversion rate, simultaneously increasing the sound wave propagation impedance to achieve 26% sound energy dissipation, achieving a 64% attenuation of vibration acceleration and synergistic suppression of mid-frequency noise.
[0076] As can be seen from Examples 1, 6, and 7, the process of high-speed molten metal impacting the pores of the preform is essentially a conversion of kinetic energy into interfacial bonding energy. When the velocity is below 3 m / s, the molten aluminum solidifies prematurely within the pores of the damping layer (filling rate < 65%), and a layer of abrupt change in acoustic impedance is formed at the unbonded interface—this not only blocks the transmission path of vibration shear force (causing a 10 μm slip between the constraint layers), but also scatters sound waves, disrupting the phase interference of the sound-absorbing holes, resulting in a loss of both vibration and acoustic energy conversion rates. Overspeed impact (> 5 m / s) induces molten turbulence, and the cavitation shock wave shatters the damping microspheres and breaks the outer shell of the phase change capsule, directly disintegrating the two energy conversion systems. Only when the impact velocity is 4 m / s (laminar flow state) penetrates the pores does the molten metal and the matrix undergo a micro-regional eutectic reaction to form a 2-3 μm metallurgical bonding layer. This interface combines a shear strength of >50MPa with an ultra-low thermal resistance of 0.018K / W, ensuring a 92% conduction efficiency of vibrational heat energy; at the same time, it replicates the sound-absorbing channels with millimeter precision (tolerance <20μm), maintaining precise wavelength control for sound wave reflection and energy dissipation.
[0077] In summary, the combination of the stable temperature field of the 22% phase change capsule, the molecular chain dissipation network of the 35% damping layer, and the metallurgical interface formed by 4m / s injection molding ensures that when the engine's sound wave radiation and structural vibration impact the housing, the stable temperature field ensures the stability of the sound-absorbing holes, converting sound energy into heat energy; the rigid layer converts vibration into shear stress, and the 35% damping ratio causes the molecular chain to slip and dissipate mechanical energy; the phase change material absorbs transient heat peaks, and the metallurgical interface introduces the calorific heat converted from noise into the heat dissipation layer. Ultimately, the sound pressure of the housing drops sharply, the vibration acceleration decays, and the engine noise is converted into a controllable heat flow that is dissipated into the environment, achieving the ultimate physical domestication of sound and vibration energy.
[0078] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for processing die-cast alloy material for hybrid engine housings, comprising the following steps: S1: A non-ferrous metal matrix composite material with both rigidity and thermal conductivity is used as the base material, and is uniformly mixed with Al-Si phase change microcapsules and pressed into a heat dissipation preform. S2: Mix the base material powder with low melting point metal wire, prepress and solidify, and heat to dissolve the metal wire to obtain a rigid layer preform; S3: Mix and press the base material powder with the damping material to obtain the damping layer preform; S4: Stack the products of S1, S2 and S3 in sequence as rigid layer preform - damping layer preform - rigid layer preform - heat dissipation preform, preheat and press them into shape.
2. The processing method of a die-cast alloy material for a hybrid engine housing according to claim 1, characterized in that: In S1, the rigidity is specifically an elastic modulus of 70-80 GPa, the thermal conductivity is specifically a thermal conductivity of 145-155 W / mK, the substrate is selected from one of high silicon aluminum alloy, aluminum-magnesium alloy or silicon-copper alloy, and the amount of phase change microcapsules added is 15%-25% of the total amount of substrate material and phase change microcapsules after the announcement.
3. The processing method of a die-cast alloy material for a hybrid engine housing according to claim 1, characterized in that: In S1, the specific preparation method of Al-Si phase change microcapsules is as follows: A1: The Al-Si alloy is ground into granules and then oxidized under high pressure to form an aluminum hydroxide transition layer; A2: The A1 product is placed in an oxygen environment and heated to transform the transition layer into an alumina shell. A3: The product A2 is immersed in silica sol and heated to allow alumina and silica to react and form a mullite shell, thus obtaining Al-Si phase change microcapsules.
4. The processing method of a die-cast alloy material for a hybrid engine housing according to claim 1, characterized in that: In the A1, the particle diameter is 20-50 μm, and the high-pressure environment is specifically 0.5-2 MPa with water vapor introduced, the temperature is 100-150℃, and the time is 0.5-1 h.
5. A method for processing a die-cast alloy material for a hybrid engine housing according to claim 4, characterized in that: In A2, the heating process specifically involves a heating rate of 20-30℃ / min, a final temperature of 700-1100℃, and a holding time of 0.5-6h; in A3, the heating temperature is 1000-1200℃.
6. A method for processing a die-cast alloy material for a hybrid engine housing according to claim 1, characterized in that: In step S2, the low-melting-point metal wire is selected from one of low-temperature aluminum welding wire, lead-tin alloy, or aluminum bronze welding wire. The pre-pressing and curing process specifically involves first cold pressing at 200-300 MPa pressure, and then hot pressing at 350-400℃ and 70-100 MPa pressure. The heating and melting temperature is 450-500℃, and the amount of low-melting-point metal wire added is 9%-15% of the total amount of base material and low-melting-point metal wire in this step.
7. A method for processing a die-cast alloy material for a hybrid engine housing according to claim 1, characterized in that: In step S3, the damping material is selected from polyimide microspheres, modified polyurethane foam, or butyl rubber / chlorinated butyl rubber. The mixing and pressing parameters are 40-50 MPa, and the damping material accounts for 30%-40% of the total damping material and substrate material in this step.
8. A method for processing a die-cast alloy material for a hybrid engine housing according to claim 1, characterized in that: In S4, the preheating parameters are to raise the temperature to 350-400℃ for 10-20 minutes. The pressing process involves placing the preheated product into the mold cavity, melting the base material at 680-720℃ and injecting it into the mold cavity at a speed of 0.2-0.5 m / s, and then applying high-speed pressurization at a speed of 3-5 m / s and a pressure of 70-100 MPa, so that the melt penetrates into the gaps between the preforms and bonds to form a whole.
9. A die-cast alloy material for a hybrid engine housing, based on the processing method according to any one of claims 1-8, characterized in that, This includes a heat dissipation layer and a sound absorption layer; The sound-absorbing layer is located near the interior of the engine housing and has a sandwich structure; the heat dissipation layer is located away from the interior of the engine housing.
10. A die-cast alloy material for a hybrid engine housing according to claim 9, characterized in that: The sound-absorbing layer sandwich structure is specifically a rigid layer-damping layer-rigid layer, and the rigid layer has a number of sound-absorbing holes.